A Case of Osteogenesis Imperfecta Type II Caused by a Novel COL1A2 Gene Mutation: Endoscopic Third Ventriculostomy to Prevent Hydrocephalus - Hachiya, Yasuo; Hayashi, Masaharu; Negishi, Takashi; Atsumi, Soh; Kubota, Masaya; Nishihara, Tetsuhiro (Neuropediatrics, 2012)
Osteogenesis imperfecta (OI) is a hereditary connective tissue disorder caused by defects in type I collagen synthesis. OI is generally classified into four types (I to IV), and the clinical prognosis varies from a lethal outcome for type II and varying deformities for type III to a normal lifespan for the other types. We describe a female patient with biochemically confirmed OI caused by a novel mutation in the COL1A2 gene. Persistence of blue sclerae supported the diagnosis of OI type II. The case was complicated with obstructive hydrocephalus, for which endoscopic third ventriculostomy (ETV) was performed. The ETV was transiently effective for the obstructive hydrocephalus. The patient subsequently developed brain atrophy, partly through ischemic events after the ETV, which appeared to contribute to maintenance of smooth circulation of the cerebrospinal fluid. We conclude that continuous and adequate medical care including ETV can facilitate long-term survival even in lethal OI type II.
Keywords: osteogenesis imperfecta; hydrocephalus; long survival; type I collagen